Association between the empirical dietary inflammatory index and cardiorespiratory fitness in Tehranian adults in 2017–2018 - Payandeh, Nastaran; Shahinfar, Hossein; Babaei, Nadia; Davarzani, Samira; Ebaditabar, Mojdeh; Djafarian, Kurosh; Shab-Bidar, Sakineh (Frontiers in Nutrition, 2022)
Background Inflammatory-related chronic diseases are increasing in Iran with high consumption of a diet containing pro-inflammatory potential and a sedentary lifestyle. The empirical dietary inflammatory index (EDII) was developed as a tool to assess dietary effects on systemic inflammation. We examined the hypothesis that specific dietary patterns reflecting systemic inflammation are associated with cardiorespiratory fitness (CRF) in Tehranian adults. Methods This cross-sectional study was carried out on 270 adults who are residents of Tehran. Dietary intake was assessed using a 168-item valid and reliable food frequency questionnaire. The EDII score was developed according to participant dietary intakes of 21-item pre-defined food groups. CRF was assessed by using a graded exercise treadmill test. Anthropometric measurements were assessed using standard methods. To discover the association between CRF and EDII, we used multivariable logistic regression analysis. Results Those who were in the third tertile of the EDII had 57% lower odds of having better VO2Max (ml/kg/min) than those in the first tertile (OR: 0.43; 95% CI: 0.16, 1.12, p = 0.01). There were no significant differences between tertiles of the EDII score in terms of VO2 (L·min) and VO2 (LBM) before and after adjusting for confounders. There was a significant decrease in VO2Max (ml/kg/min) across tertiles of the EDII after controlling for covariates (p-value = 0.04). There was a significant inverse association between the EDII score and VO2Max (ml/kg/min) (β = −0.35, p = 0.001). Conclusions Our finding demonstrated that a higher EDII might be associated with lower CRF in Tehranian adults. Prospective studies are needed to shed light on the causal link between the EDII and CRF.